Higher vedolizumab serum levels do not increase the risk of adverse events in patients with inflammatory bowel disease. (2nd July 2020) - Sengupta, Neil K.; Azizov, Ahmad; Halder, Smita; Xenodemetropoulos, Ted; Armstrong, David; Tse, Frances; Marshall, John K.; Narula, Neeraj
Abstract: Background: Although its mechanism of action may confer a safety benefit, vedolizumab has still been associated with adverse events (AE). We investigated whether inflammatory bowel disease (IBD) patients with higher trough vedolizumab serum levels experienced an increased risk of AEs. Methods: This was a retrospective study of 76 IBD patients with at least one measurement of serum vedolizumab available. Vedolizumab levels ranged from <3.5 mcg/mL to 87.2 mcg/mL (median = 15.8 mcg/mL). The primary outcome was the rate of overall AEs. Secondary outcomes included the rates of infections, dermatologic reactions, infusion reactions, and other AEs. Multivariate logistic regression analysis was performed to evaluate the relationship between serum vedolizumab levels and AEs. Results: 19 patients out of 76 reported AEs. In patients with higher vedolizumab levels, there were 10 AEs reported out of 38 patients, which was not significantly different from the 9 AEs reported in 38 patients with lower vedolizumab levels (26.3% vs. 23.7%, p  = .79). After adjustment for potential covariates, IBD patients with higher vedolizumab levels did not have higher odds of an AE than patients with lower levels (OR 0.92, 95% CI 0.30–2.81). Longer duration of therapy had higher odds of AEs, (OR of 1.04 at 95% CI 1.00–1.09, p  = .0494 per additional month). None of the other variables were associated with a greater risk of AEs. Conclusions: There does not appear to be an increased risk of adverse events in IBD patients with higher vedolizumab levels, but duration of therapy may increase the risk of AEs.